2016
DOI: 10.1021/acscatal.6b00848
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Metal-Based Catalysis in Supercritical Carbon Dioxide as Reaction Medium

Abstract: Above 31.1 °C and 73.8 bar, carbon dioxide reaches the supercritical condition, being transformed into a fluid (scCO2) that has gained interest in the last decades as reaction medium for several transition metal-catalyzed organic transformations. The main feature of this fluid stands on its capability to dissolve large amounts of other gases such as hydrogen, carbon monoxide, ethylene or even methane and light alkanes. In this manner, very high concentrations of these reactants are available for catalysis. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 174 publications
0
25
0
Order By: Relevance
“…[30] Presently,m any examples of synthesis of different compounds as well as the separation of products from the reaction system by using scCO 2 have been reported and offer ac hance to make processes environmentally friendly by reduction of volatile organic solvents ande liminationo fs eparation steps. [31] The solubilityo fc ompounds in scCO 2 mainly depends on their polarity,volatility,and molecular weight. Moreover,different functional groups attachedt ot he compounds can influence their solubility in this green solvent.…”
Section: Hydroboration Of Terminal Alkynes Under Optimized Conditionsmentioning
confidence: 99%
“…[30] Presently,m any examples of synthesis of different compounds as well as the separation of products from the reaction system by using scCO 2 have been reported and offer ac hance to make processes environmentally friendly by reduction of volatile organic solvents ande liminationo fs eparation steps. [31] The solubilityo fc ompounds in scCO 2 mainly depends on their polarity,volatility,and molecular weight. Moreover,different functional groups attachedt ot he compounds can influence their solubility in this green solvent.…”
Section: Hydroboration Of Terminal Alkynes Under Optimized Conditionsmentioning
confidence: 99%
“…[a] EntryC atalyst Ligand Yield of 1 [%] [b] Yield of 2 [%] [b] 1Z ChemSusChem 2017ChemSusChem , 10,1501ChemSusChem -1508 www.chemsuschem.org the reactions ystem in situ as the standard reactionc onditions. [24] Like MeCN, CO 2 behaves as asolvent that diluted the components of the reactions ystem. Even if ac atalyst and ligand are employed,h igh temperatures (> 100 8C) are often required for carbamate synthesis directly from an amine, CO 2 ,a nd TMOS.…”
Section: Resultsmentioning
confidence: 99%
“…The low yield of 1 at high CO 2 pressures suggested that ah igh-density CO 2 condensate formed from the gas phase. [24] Like MeCN, CO 2 behaves as asolvent that diluted the components of the reactions ystem. [25] Figure2 shows that the best resultsw ere obtained at aC O 2 pressureo f5MPa, whichp rovided the highest yield and selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, a substantial research effort has been made to replace these conventional harmful solvents by sustainable media . The sustainable media applied for synthetic organic processes are principally supercritical carbon dioxide, bio‐based solvents such as glycerol, poly(ethylene glycol)s, ionic liquids, and deep eutectic solvents …”
Section: Optimization Of the Reaction Conditions On The Model Reactionmentioning
confidence: 99%